Record of Discussions Fifty Third Meeting National Development Council 29th May 2007 - Planning Commission (Planning Commission Government of India, 2007)
The Fifty-Third Meeting of the National Development Council (NDC), held on May 29, 2007, focused on revitalizing India’s agriculture sector to ensure food security, enhance productivity, and improve farmer livelihoods. The meeting highlighted challenges such as stagnant growth, yield gaps, inadequate irrigation, and rural distress, including farmer indebtedness and suicides. Key resolutions emphasized the launch of the Food Security Mission, increased Central funding, district- and state-level agricultural plans, and restructuring irrigation and fertilizer subsidies. Crop diversification, modern extension services, technological research, and market reforms were prioritized. The meeting underscored collaborative action between Central and State governments to achieve 4% annual agricultural growth, sustainable resource management, and equitable development for rural communities.
Government of India Planning Commission New Delhi
Keywords: National Development Council; Agricultural Growth; Food Security; Irrigation Infrastructure; Farmer Welfare; Crop Diversification; Extension Services; Fertilizer Subsidy; Research and Technology; State Agricultural Plans; Market Reforms; Credit Support